KÊMBANG JAMBÉ, GÊNDHING KÊTHUK 2 KÊRÊP MINGGAH 4 LARAS SLÉNDRO PATHÊT SANGA: KAJIAN GARAP GENDÈR - Rika Irawati; Siswati (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2024)
The article entitled “Kêmbang Jambé, gêndhing kêthuk 2 kêrêp minggah 4 laras sléndro pathêt sanga: Kajian Garap Gendèr” was compiled to explain the study of gendèran Kêmbang Jambé. Kêmbang Jambé is one of the Surakartan style gendhing repertoires which is included in the Kepatihan gendhing. In this article, the author offers the gêndhing Kêmbang Jambé of Mloyowidodo’s version, guided by the garap of Surakartan style traditional karawitan, including the garap of mrabot, ciblon irama wiled, and rangkep. This artwork research is qualitative research. Data collection has been done through literature studies, observation, and interviews. The series of the gendhing in this artwork thesis has been played referring to the concept of Surakartan style karawitan. The concept that has been used are garap, mrabot, pathêtm and mungguh. The result of the study of Mloyowidodo’s version of garap gendèr gêndhing Kêmbang Jambé is there are several balungans that can be an alternative to the garap ciblon irama rangkep. This study applies céngkok and garap which refers to the other Surakartan style gendhing, to be applied in the irama rangkep. The author refers to the case of garap in the gendhing Onang-onang, then applies it to the gendhing Kêmbang Jambé by paying attention to all aspects, including kemungguhan.